Kronik sosyal izolasyon modelinde agmatinin etkilerinin araştırılması - Shabani, Ali (My University, 2020)
Amaç: Agmatin santral sinir sisteminde yaygın bulunan, nörotransmiter/ nöromodülatör fonksiyonları olan endojen bir maddedir. Daha önce antidepresan ve anksiyolitik etkileri araştırılmış olan agmatinin bu çalışmada sıçanlarda kronik sosyal izolasyon (Sİ) modelinde etkilerinin araştırılması amaçlanmıştır.Gereç ve yöntem: Sprague Dawley sıçanlar control, Sİ, Sİ+Fluoksetin (FLU) ve Sİ+Agmatin (AGM) 4 gruba (n=8/ grup) ayrılmıştır. Hayvanlar tek olarak kafeslere alınarak 5 hafta süre ile izole edilmişler, hemen ardından kontrol ve Sİ gruplarına serum fizyolojik, Sİ+FLU ve Sİ+AGM gruplarına ise 15mg/ kg FLU veya 40mg/ kg AGM 10 gün süreyle günde tek doz olacak şekilde intraperitoneal olarak verilmiştir. Açık alan (open field; OF), yükseltilmiş artı labirent (elevated plus maze; EPM), yeni obje tanıma (novel object recognition; NOR) ve bilye gömme (marble burying; MB) testleri yapılmıştır. Tüm hayvanlar dekapite edilerek moleküler analizler için prefrontal korteks diseksiyonu yapılmıştır. Bulgular: Sİ grubunda kontrol grubu ile karşılaştırıldığında OF testinde toplam aktivitede azalma, EPM testinde kapalı kollara geçiş sayısını ve süresini arttırmış, NOR testinde ayırd etme indeksinde bozulma ve MB testinde bilye gömmeyi artırmıştır. Bu değişikliklerin FLU tedavi grubunda kısmen, AGM tedavi grubunda ise tamamen geri döndüğü görülmüştür. Sİ grubunda IL-1B ve NF-kB mRNA ekspresyonlarında artış olduğu bu artışın FLU tedavi grubunda kısmen, AGM tedavi grubunda ise tamamen baskılandığı görülmüştür.Sonuçlar: Bu çalışmanın sonuçları AGM’nin Sİ ile meydana gelen değişiklikler üzerinde etkili olduğunu ve bu etkiyi kısmen proinflamatuar sitokinlerin üretimini baskılayarak yapabileceğini göstermiştir.İÇİNDEKİLER1. ÖZET ................................................................................................................…. 12. ABSTRACT …....................................................................................................... 23. GİRİŞ VE AMAÇ ................................................................................................. 34. GENEL BİLGİ ……………….............................................................................. 55. GEREÇ VE YÖNTEM ……….....…..………………………………….…..…. 266. BULGULAR …………………………………………………………….....…… 337. TARTIŞMA VE SONUÇLAR ………………………………......…………..… 388. KAYNAKLAR ....…………………….....…………………….…..………….…. 43

Investigating effects of agmatine in chronic social isolation model Student’s name: Ali ShabaniSupervisor: Prof. Dr. Feyza AriciogluDepartment: PharmacologyAim of study: Agmatine is an endogenous molecule that is widely available in the central nervous system and has neurotransmitter/ neuromodulator functions. Previous studies researched the antidepressant and anxiolytic effects of agmatine so this study aimed to investigate its effects on chronic social isolation model (SI).Material and methods: Sprague Dawley rats were separated to 4 groups (n=8/ group) as control, SI, SI+Fluoxetine (FLU) and SI+Agmatine (AGM). Animals were isolated in individual cages for 5 weeks. Right after that, control and and SI groups were given serum physiologic, while SI+FLU and SI+AGM groups were given 15mg / kg FLU or 40mg / kg AGM for 10 days as one daily intraperitoneal dose. Open field (OF), elevated plus maze (EPM), novel objects recognition (NOR) and marble burying (MB) tests were applied. All animals were decapitated and prefrontal cortex dissection was performed for molecular analysis.Results: SI group when compared to the control group showed less total activity in OF test, more entrances and time spent into closed arms in EPM test, corruption in the discrimination index in NOR test and exessive burying in MB test. These changes were partially suppressed in FLU therapy group while totally suppressed in AGM therapy group. The elevated expression of IL-1B and NF-kB mRNA shown in SI group was also suppressed partially in FLU therapy group and totally in AGM therapy group.Conclusion: This study shows that agmatine expresses effects against changes caused by SI and these effects may be partially caused by the suppression of proinflammatory cytokines production.CONTENTS1. ÖZET ................................................................................................................…. 12. ABSTRACT …....................................................................................................... 23. INTRODUCTION and AIM ................................................................................ 34. Stress ....................................................................................................…............ 54.1.1. History of stress research ………………………………………………….…. 54.1.2. HPA and SAM axes in stress response ...……………………………………...74.1.3. Stress and neurotransmission ...…………...………………………………… 114.1.4. Stress and metabolism …………...………………………………………….. 124.2. Social isolation stress ……………………………………………………….… 124.2.1. Social isolation effect on neuroplasticity and neurotrophic factors ................ 134.2.2. Social isolation stress, cytokines and immune-inflammatory response ......... 164.2.3. Social isolation and endocrine system …………………………………….... 18 4.3. Agmatine ............................................................................................................ 194.3.1. Structure, metabolism and availability ………………....…….…….….…… 194.3.2. Effects of agmatine on nervous system .......................................................... 204.3.3. Effects of agmatine on CNS disorders ……………………………...………. 214.3.3.1. Drug and substance addiction …………………………………………….. 21 4.3.3.2. Alzheimer's disease (AD) and other neurodegenerative diseases ….……... 22 4.3.3.3. Agmatine and psychiatric disorders ………………………………….…… 22 4.3.3.3.1. Schizophrenia ……………………………………………………….…... 22 4.3.3.3.2. Depression and bipolar disorder ………………………………………... 22 4.3.3.3.3. Anxiety ……………………………………………………………….…. 23 4.3.3.3.4. Other CNS disorders ………………………………………………….… 23 4.3.4. Agmatine as a potential stress pharmacological treatment ............................. 244.3.5. Agmatine neuroinflammatory effects …………………………………...….. 245. MATERIALS and METHODS ...…..………………………………….…..…. 265.1. Materials ...………………………………………………………………….… 265.2. Animals and housing …..………………………………….…………..……… 265.3. Social isolation protocol …...…………………………………………………. 265.4. Experimental design and treatments …...……………………………….…….. 27 5.5. Behavioral tests …...………………………………………………………...… 285.5.1. Open field test (OF) test …...……………..………….……….………..……. 285.5.2. Elevated plus maze (EPM) test …...……………...……………….…...……. 295.5.3. New object recognition (NOR) test …...………………………………...….. 295.5.4. Marble burying (MB) test …...………………………………………..…….. 305.6. Collection of tissue samples ………………………………………………….. 315.7. Real-time PCR analysis of gene expressions …………………………………. 315.8. Statistical Analysis ……………………………………………………...…….. 326. RESULTS ……………………………………………………………........…… 336.1. Body weight ………………………………………………….…...…………... 336.2. Behavioral Data …...…………………………………………...…..……...….. 336.2.1. Locomotor activity results …...…………………………………...………… 336.2.2. EPM Results ……………………………………………….………….…..… 346.2.3. MB test results ……………………………………………...………...….…. 356.2.4. NOR test results …………………………………………………………..… 366.3. Molecular results …………………………………………………….………... 366.3.1. IL-1B mRNA levels in PFC ………………………………………………… 366.3.2. NF-kB mRNA levels in PFC …………………………………….….....…… 377. DISCUSSION and CONCLUSION ………………………………......……… 388. REFERENCES ....…………………….....…………………….…………….…. 43
Keywords: Agmatin; Farmakoloji; fluoksetin; fluoxetine; Health; Pharmacology; proinflamatuar sitokinler Agmatine; proinflammatory cytokines; Sağlık; social isolation; sosyal izolasyon